ASSESSING LOCAL TAX CONTRIBUTIONS TO LOCAL OWN REVENUE: EVIDENCE IN ONE REGION IN INDONESIA - Dendy Syaiful Akbar; Yat Rospia Brata; Elin Herlina; Benny Prawiranegara; Faizal Haris Eko Prabowo (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2019)
The purpose of this study is to analyze the size of the contribution of local taxes to the Ciamis Regency local own revenue. In this study, the formula for the ratio of local tax contribution to local own revenue was formulated. The research method used is a descriptive method with a quantitative approach. Measurement of contributions of local taxes on local own revenue is drawn from the local own revenue structure which consists of local taxes, regional levies, separated regional wealth results, and other legitimate regional income. The results of the study show that the contribution of local taxes to local own revenue is in the very low and low category, because during the 2013-2015 fiscal year the figure was below 26%, while in the 2016-2017 fiscal year it reached a number of 26% -50%. The low contribution of local taxes to local own revenue is due to restaurant taxes stipulated through regional regulation No. 5 of 2011, namely the imposition of a 10% tax on each transaction with consumers is still a lot of rejection from most restaurant managers, with the reason of fear of a decline in consumers.